Prospects of barcoding the Italian wild dendroflora: oaks reveal severe limitations to tracking species identity. - Piredda, Roberta; Simeone, Marco C; Attimonelli, Marcella; BELLAROSA, Rosanna; Schirone, Bartolomeo (Molecular ecology resources, 2011)
DNA barcoding may be particularly important in influencing ecology, economic issues, and the fundamental crisis facing biodiversity as a standardized, species-level identification tool for taxonomy assessment. Trees play important roles in the conservation of many land ecosystems, the wood trade, and the definition of biogeographical processes; nevertheless, peculiar biological, evolutionary and taxonomical features will probably constitute an intriguing challenge to barcoders. We examined whether four marker regions (trnh-psba, rbcL, rpoc1, matK) proposed by the Consortium for the Barcode of Life (CBOL) matched species taxonomy in a preliminary tree biodiversity survey of Italian forested land. Our objective was to provide a test of future in situ applications of DNA barcodes by evaluating the efficacy of species discrimination under the criteria of uniformity of methods and natural co-occurrence of the species in the main forest ecosystems. Fifty-two species were included in a floristic study. We obtained 73% total discrimination success, with trnH-psbA as the best performing marker and oaks as the least responsive plants to the markers used. A further taxon-based study of Quercus (thirty specimens, 12 species) revealed that this genus is refractory to barcoding (0% discrimination success), a probable consequence of low variation rate at the plastid genome level, hybridization, and the incidence of biogeography. We conclude that some species-rich tree genera in small geographical regions may prove exceptionally difficult to barcode. Until more efficient markers are developed, we recommend that improved and diversified sampling (multiple locations of sympatric and co-occurring congenerics) be embraced as a timely and important goal for the precise assessment of haplotype specificity to facilitate the productive application of barcoding in practice.
Keywords: DNA barcoding; forest trees; Italy; Quercus; regional sampling

Proteomics research on forest trees, the most recalcitrant and orphan plant species. - Abril, Nieves; Gion, Jean-Marc; Kerner, René; Müller-Starck, Gerhard; Cerrillo, Rafael M. Navarro; Plomion, Christophe; Renaut, Jenny; Valledor, Luis; Jorrin-Novo, Jesús V. (Phytochemistry, 2011)
The contribution of proteomics to the knowledge of forest tree (the most recalcitrant and almost forgotten plant species) biology is being reviewed and discussed, based on the author's own research work and papers published up to November 2010. This review is organized in four introductory sections starting with the definition of forest trees (1), the description of the environmental and economic importance (2) and its derived current priorities and research lines for breeding and conservation (3) including forest tree genomics (4). These precede the main body of this review: a general overview to proteomics (5) for introducing the forest tree proteomics section (6). Proteomics, defined as scientific discipline or experimental approach, it will be discussed both from a conceptual and methodological point of view, commenting on realities, challenges and limitations. Proteomics research in woody plants is limited to a reduced number of genera, including Pinus, Picea, Populus, Eucalyptus, and Fagus, mainly using first-generation approaches, e.g., those based on two-dimensional electrophoresis coupled to mass spectrometry. This area joins the own limitations of the technique and the difficulty and recalcitrance of the plant species as an experimental system. Furthermore, it contributes to a deeper knowledge of some biological processes, namely growth, development, organogenesis, and responses to stresses, as it is also used in the characterization and cataloguing of natural populations and biodiversity (proteotyping) and in assisting breeding programmes.
The following values have no corresponding Zotero field: publisher: Elsevier Ltd accession-num: 21353265
Keywords: Forest tree proteomics; forest trees; Plant proteomics; Woody plants

Large-scale environmental correlates of forest tree distributions in Catalonia (NE Spain) - Thuiller, Wilfried; Vayreda, Jordi; Pino, Joan; Sabaté, Santi; Lavorel, Sandra; Gracia, Carles (Global Ecology and Biogeography, 2003)
Aim To explore the environmental correlates of tree species distributions in Catalonia according to the chorological status of the species. Location The study area is the region of Catalonia, in northeastern Spain. Methods We used presence-absence data for 24 species, sampled in random plots distributed throughout forests of Catalonia. A climate model for the Catalonia region provided environmental variables. We used classiﬁcation tree analysis to explore the environmental correlates of the realized niches of tree species. The predictive accuracy of the models was assessed using the ROC curve approach. Potential distribution maps of tree species were generated for the whole Catalonia region. Results Models were ranked from low to high accuracy for the 24 species. Differences in accuracy among species were related to the chorological status of species. Zonal species, or species at the core of their range (Mediterranean and SubMediterranean species), were generally well predicted, while extrazonal species, or species at the edge of their range, were predicted only moderately well. Mediterranean species distributions showed good correlations with extreme temperatures and annual precipitation. Main conclusions The above trends conﬁrmed the difﬁculty of identifying the realized niche of species at the edges of their ranges. In contrast, Mediterranean and Sub-Mediterranean species, which were at the core of their range, were well-predicted, conﬁrming the importance of extremes of temperature and annual precipitation as effective surrogates for variables having more direct physiological roles in limiting the ability of plants to survive and grow. Maps of potential tree distributions allowed us to deﬁne suitable habitats and to highlight areas where species have been planted outside their natural distribution.
Keywords: chorology; classification tree analysis; environmental gradients; forest trees; potential distribution maps; realized niche; Spain

Large-scale environmental correlates of forest tree distributions in Catalonia (NE Spain) - Thuiller, Wilfried; Vayreda, Jordi; Pino, Joan; Sabaté, Santi; Lavorel, Sandra; Gracia, Carles (Global Ecology and Biogeography, 2003)
Aim To explore the environmental correlates of tree species distributions in Catalonia according to the chorological status of the species. Location The study area is the region of Catalonia, in northeastern Spain. Methods We used presence-absence data for 24 species, sampled in random plots distributed throughout forests of Catalonia. A climate model for the Catalonia region provided environmental variables. We used classiﬁcation tree analysis to explore the environmental correlates of the realized niches of tree species. The predictive accuracy of the models was assessed using the ROC curve approach. Potential distribution maps of tree species were generated for the whole Catalonia region. Results Models were ranked from low to high accuracy for the 24 species. Differences in accuracy among species were related to the chorological status of species. Zonal species, or species at the core of their range (Mediterranean and SubMediterranean species), were generally well predicted, while extrazonal species, or species at the edge of their range, were predicted only moderately well. Mediterranean species distributions showed good correlations with extreme temperatures and annual precipitation. Main conclusions The above trends conﬁrmed the difﬁculty of identifying the realized niche of species at the edges of their ranges. In contrast, Mediterranean and Sub-Mediterranean species, which were at the core of their range, were well-predicted, conﬁrming the importance of extremes of temperature and annual precipitation as effective surrogates for variables having more direct physiological roles in limiting the ability of plants to survive and grow. Maps of potential tree distributions allowed us to deﬁne suitable habitats and to highlight areas where species have been planted outside their natural distribution.
Keywords: chorology; classification tree analysis; environmental gradients; forest trees; potential distribution maps; realized niche; Spain